Expansion of circulating NKG2D+ effector memory T-cells and expression of NKG2D-ligand MIC in granulomaous lesions in Wegener's granulomatosis. - Capraru, D; Müller, A; Csernok, E; Gross, W; Holl-Ulrich, K; Northfield, J; Klenerman, P; Herlyn, K; Holle, J; Gottschlich, S; Voswinkel, J; Spies, T; et al. (2008)
Expansion of circulating CD28- T-cells reminiscent of effector memory T-cells (T(EM)) has been reported in Wegener's granulomatosis (WG) recently. To investigate the role of T(EM) in WG, we analyzed the expression of the activating NK-receptor NKG2D and its ligand MIC on circulating T(EM) and in granulomatous lesions, respectively. NKG2D was anomalously expressed and preferentially detected on circulating CD4+CD28- T(EM) in WG. Compared to healthy controls, T(EM) display a more activated phenotype potentially favoring unbalanced proinflammatory responses in WG. Cluster-like formations of "Wegener's autoantigen" PR3 were surrounded by NKG2D+ and NKG2D-ligand MIC+ cells in WG-granulomata, but not in disease controls. Further, IL-15 - known to drive T(EM) differentiation and proliferation--was also expressed in WG-granulomata. Thus, through acquisition of NK-like "innate" properties, IL-15 stimulated NKG2D+ T(EM) could interact with MIC+ cells within WG-granulomata, thereby sustaining inflammation and autoimmunity and promoting self-perpetuating pathology in WG.